AI-POWERED PREDICTIVE ANALYTICS FOR MULTI-CLOUD MANAGEMENT - Vedaswaroop Meduri, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
Integrating artificial intelligence with cloud computing represents a transformative advancement in modern information technology infrastructure, fundamentally reshaping how organizations manage and optimize their cloud resources. This comprehensive article explores the revolutionary impact of AI-driven solutions across various aspects of cloud computing, including resource management, optimization strategies, operational technologies, and industry leadership. The article examines how leading technology providers have implemented AI capabilities to enhance their cloud platforms, demonstrating significant efficiency, performance, and cost optimization improvements. The article further investigates the business implications of this technological convergence, highlighting its role in driving innovation, improving operational excellence, and creating new opportunities across diverse industry sectors.